Annual conference with international participation "Development and registration of biotechnological drugs" will be held in Moscow on June 25 - article Editorial (Разработка и регистрация лекарственных средств)
The conference will take place on June 25 in Moscow in a live format. The conference is organized by LLC "CPHA" and the scientific and production journal Drug development & registration.